2009
DOI: 10.1371/journal.ppat.1000479
|View full text |Cite
|
Sign up to set email alerts
|

Selective Processing and Metabolism of Disease-Causing Mutant Prion Proteins

Abstract: Prion diseases are fatal neurodegenerative disorders caused by aberrant metabolism of the cellular prion protein (PrPC). In genetic forms of these diseases, mutations in the globular C-terminal domain are hypothesized to favor the spontaneous generation of misfolded PrP conformers (including the transmissible PrPSc form) that trigger downstream pathways leading to neuronal death. A mechanistic understanding of these diseases therefore requires knowledge of the quality control pathways that recognize and degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
109
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(116 citation statements)
references
References 54 publications
7
109
0
Order By: Relevance
“…This mechanism clears misfolded or aggregated protein from the Golgi and transfers them to the lysosome for degradation (Anelli and Sitia, 2008;Arvan et al, 2002). This pathway has previously been implicated in the clearance of misfolded PrP isoforms generated by inherited prion disease mutations or pharmacological manipulation of PrP trafficking in neuronal cells (Ashok and Hegde, 2009;Gilch et al, 2001). The results presented here extend these findings to infectious PrP isoforms, where PrP Sc formed following inocula exposure at the cell surface enters the Golgi via the retrograde pathway before being targeted for degradation.…”
Section: Alternative Fates Of Newly Formed Prpsupporting
confidence: 71%
“…This mechanism clears misfolded or aggregated protein from the Golgi and transfers them to the lysosome for degradation (Anelli and Sitia, 2008;Arvan et al, 2002). This pathway has previously been implicated in the clearance of misfolded PrP isoforms generated by inherited prion disease mutations or pharmacological manipulation of PrP trafficking in neuronal cells (Ashok and Hegde, 2009;Gilch et al, 2001). The results presented here extend these findings to infectious PrP isoforms, where PrP Sc formed following inocula exposure at the cell surface enters the Golgi via the retrograde pathway before being targeted for degradation.…”
Section: Alternative Fates Of Newly Formed Prpsupporting
confidence: 71%
“…Although some alterations in processing and cleavage were observed, the presence of the G113V or A116V mutation did not alter the localization or expression of PrP. Furthermore, similar to MoPrP C , PrP C associated with G113V and A116V was shown here to be detergent soluble (in agreement with a previous study [60]), and separation of PrP by velocity gradient sedimentation revealed no gross differences compared to MoPrP.…”
Section: Discussionsupporting
confidence: 90%
“…[19][20][21] In addition, PrP C familial or artificial mutants that accumulate intracellularly are also neurotoxic. 22,23 Dimerization may help preventing fatal accumulation of intracellular PrP C . According to our model, we predict that promoting PrP C dimerization in the secretory pathway may help fighting neurotoxic insults, including the neutralisation of β-sheet oligomers (Fig.…”
Section: 6mentioning
confidence: 99%